2011
DOI: 10.1002/ana.22483
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal and delivery outcomes in women with multiple sclerosis

Abstract: ObjectiveTo determine (1) whether the risk of adverse neonatal and delivery outcomes differs between mothers with and without multiple sclerosis (MS) and (2) whether risk is differentially associated with clinical factors of MS.MethodsThis retrospective cohort study analyzed data from the British Columbia (BC) MS Clinics' database and the BC Perinatal Database Registry. Comparisons were made between births to women with MS (n = 432) and to a frequency-matched sample of women without MS (n = 2,975) from 1998 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
73
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 30 publications
6
73
1
6
Order By: Relevance
“…[3][4][5][6] Although not all agree, more recent studies found no link between MS and adverse perinatal outcomes. [7][8][9][10] However, the durations of birth hospitalization were not examined in these studies. To our knowledge, only 2 studies have examined birth hospitalization in MS 4,11 ; both were from the United States and reported longer hospital stays for mothers with MS 4,11 and their newborns 11 compared with the general population.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[3][4][5][6] Although not all agree, more recent studies found no link between MS and adverse perinatal outcomes. [7][8][9][10] However, the durations of birth hospitalization were not examined in these studies. To our knowledge, only 2 studies have examined birth hospitalization in MS 4,11 ; both were from the United States and reported longer hospital stays for mothers with MS 4,11 and their newborns 11 compared with the general population.…”
mentioning
confidence: 99%
“…This cohort of mothers and newborns has been described previously. 7 Briefly, births were classified as "births to MS mothers" if women had a neurologist-confirmed diagnosis of laboratory-supported or clinically definite MS (Poser 16 or McDonald 17 criteria) with disease onset before delivery. Birth hospitalization data of MS mothers were obtained by linking the BCMS database to the BCPDR at the individual level via the Personal Health Number, a unique identifier assigned to all residents of BC, verified by maternal names and dates of birth.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple sclerosis often manifests in early adulthood (Compston & Coles, 2002) with an average onset age of 32 years, (Shirani, Zhao, Kingwell, Rieckmann, & Tremlett, 2012) making pregnancy issues of real importance in women with MS. Studies have shown that between 1/5 and 1/3 of women with MS bear children after disease onset, (Runmarker & Andersen, 1995; Weinshenker, Hader, Carriere, Baskerville, & Ebers, 1989) making the effect of maternal MS on pregnancy outcomes relevant to patients, their family members, and health care professionals (van der Kop et al., 2011). In the past, pregnancy was discouraged in women with MS; however recent studies have shown pregnancy as having a potentially beneficial role on MS relapse rates with no effects on long‐term progression of the disease (Confavreux, Hutchinson, Hours, Cortinovis‐Tourniaire, & Moreau, 1998; Koch, Uyttenboogaart, Heersema, Steen, & De Keyser, 2009; Vukusic et al., 2004).…”
Section: Introductionmentioning
confidence: 99%